Rural Household Food Security Status: The Case of Laelay Maichew Woreda, Tigray - Weldearegay , Shishay Kahsay (Asian Accounting and Auditing Advancement, 2017)
The study was conducted in Tigray, Laelay Maichew woreda to assess the food security status of rural households. Different concepts and empirical findings are profoundly organized and presented. Both quantitative and qualitative methods were used. The analysis was made from primary and secondary data. Multi-stage random sampling method was employed to select respective agro-ecologies, Administrative kebeles, and households. Primary data were gathered using survey questionnaires, key informant interviews, focus group discussions, and observation. 150 (107 male, 43 female) households were used for the survey. While secondary data were collected from different published and unpublished materials. Data were analyzed using Household Food Balance Model (HFBM) and descriptive statistics. GIS is also used for mapping the study area. The result of HFBM analysis indicates that 22.7% of the households achieved the daily recommended calorie intake/adult equivalent/ day (2,100 kcal) while, 77.3% of households are found to be below the daily recommended calorie intake. The average calorie intake of the households covers only 56.2%. Based on the household head, female-headed households are found to be more food insecure than their male counterpart. So, the government should exhaustively work on promoting irrigation, providing credit, and subsidizing the farmers in the area of the agricultural sector to solve the problem of food insecurity. Moreover, the government should give due emphasis to female-headed households to empower them economically.